Do caldeirão de culturas ao buffet de diversidade cultural: os usos das “brasilidades” como discurso na moda contemporânea - Miqueli Michetti (Ciências Sociais Unisinos)
The article analyzes the transformation of representations of Brazil in the context of globalization. From a field research conducted among agents in charge of the creation and simultaneous globalization of the discourse about the existence of a “Brazilian fash- ion”, we could perceive current uses of Brasilianness in global and market terms. Such uses reveal a passage from the “mestizo” to the “diverse” as the typical characteristic of Brazilianness, a notion that is now conceived in its plural form. This conception is based on a perspective that tries to enumerate differences rather than subsume them into a single type, since the enumeration of the so-called national diversity would be the most convenient posture to adopt within the world market of symbolic goods, in which the notion of “cultural diversity” currently takes prime position.